ΜΙΧΑΛΗΣ ΧΡΥΣΑΝΘΟΠΟΥΛΟΣ, Υπερρεαλιστικά εγκώμια υπερρεαλιστών: Ανταγωνισμός μεταξύ Διοσκούρων; - Χρυσανθόπουλος, Μιχάλης (Σύγκριση/Comparaison/Comparison, 2022)
Surrealist “praises” (encomia) of surrealists: Empeirikos and Engonopoulos compete? The purpose of the paper is to explore the way the Greek surrealists, Andreas Empeirikos and Nikos Engonopoulos, use the form of the “praise” (encomium) in a fashion that relates to the Ancient Greek tradition and to its Renaissance revival (e.g. Erasmus, “Praise of Folly”), in order to establish the basic principles of their approaches, to deal with negative criticism of their work, to underscore the merits of the ideas and the work of their seniors, but, also, to playfully criticise them and, last but not least, to support and praise each other. The period examined in detail is that from 1935 to 1945, while emphasis is laid on Empeirikos’ long “praise” of Engonopoulos published in 1945, which redrew the rules. The surrealist “praise” is examined as a “agonistic” form, as a competition between poets and artists and as a defensive weapon against malevolent attacks from critics.